2014
DOI: 10.1002/dvdy.24105
|View full text |Cite
|
Sign up to set email alerts
|

Expression of actin‐binding proteins and requirement for actin‐depolymerizing factor in chick neural crest cells

Abstract: Background Neural crest cells are multipotent cells that migrate extensively throughout vertebrate embryos to form diverse lineages. Cell migration requires polarized, organized actin networks that provide the driving force for motility. Actin-binding proteins that regulate neural crest cell migration are just beginning to be defined. Results We recently identified a number of actin-associated factors through proteomic profiling of methylated proteins in migratory neural crest cells. Here, we report the prev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 63 publications
0
10
0
Order By: Relevance
“…This category included several proteins that are important for regulating cell migration, such as actin-depolymerizing factor, myosin 9, tropomyosin α-1, and several forms of tubulin ( Fig. 6 B ; Vermillion et al, 2013 ).…”
Section: Resultsmentioning
confidence: 99%
“…This category included several proteins that are important for regulating cell migration, such as actin-depolymerizing factor, myosin 9, tropomyosin α-1, and several forms of tubulin ( Fig. 6 B ; Vermillion et al, 2013 ).…”
Section: Resultsmentioning
confidence: 99%
“…Stress fibers are associated with Myosin (Tojkander et al, 2012), in our microarray we found many myosins highly down-regulated, especially the heavy chains (MYH1 and MYH6) or up-regulated, especially their binding proteins (MYH3, MYBPC and MYL10). Another important set of molecules (tropomyosin-1 and cofilin or ADF), have been shown by Gammill and co-workers to be expressed in pre-migratory and migratory neural crest cells (Vermillion et al, 2014). They found cofilin to be necessary for EMT but not for NCC migration.…”
Section: Discussionmentioning
confidence: 99%
“…Calponin protein expression has been suggested to be involved in neural cell contractility, proliferation, and migration (Represa et al, 1995 ; Ferhat et al, 1996 ; Ulmer et al, 2013 ). Similarly, destrin is also an actin-depolymerizing protein, which is closely related to Cofilin1 (Hatanaka et al, 1996 ) with a similar peptide sequence to the ADF (actin depolymerizing factor) protein (Hawkins et al, 1993 ), which is implicated in the regulation of neural crest cell migration (Vermillion et al, 2014 ). Along the same line, among the altered proteins Tubulin protein family including Tubulin α and Tubulin β (2a and 2c) also appears in high abundance (Supplemental Table 1 and Data Sheet 1 in the Supplementary Material).…”
Section: Discussionmentioning
confidence: 99%